Endobronchial One-Way Valve Therapy Facilitates Weaning from Extracorporeal Membrane Oxygenation in a Patient with ARDS and Persistent Air Leak - Alessandro Ghiani; Matthias Hansen; Konstantinos Tsitouras; Claus Neurohr (Case Reports in Critical Care)
Prolonged pulmonary air leak (PAL) is a common clinical problem, associated with significant morbidity and mortality. There are numerous reports of treatment of PAL using endobronchial valves (EBV) in respiratory stable patients, but only few reports on critically ill patients, and there is virtually no practical knowledge in the treatment of PAL in mechanically ventilated patients with acute respiratory distress syndrome (ARDS), treated with veno-venous extracorporeal membrane oxygenation (vvECMO). We describe a case where EBV placement was performed in a patient with ARDS and PAL, treated with mechanical ventilation and vvECMO. Despite a lung protective ventilation strategy, a persistent air leak along with a large left-sided pneumothorax was observed. After bronchoscopic localisation of the fistula, two endobronchial valves were inserted into the left upper lobe, leading to an immediate decrease in the air flow and reexpansion of the left lung. During the following two weeks, the patient was weaned from vvECMO, and after another three weeks, complete liberation from mechanical ventilation was accomplished. EBV placement seems to be a safe method even in the presence of coagulopathy and may facilitate mechanical ventilation and weaning from vvECMO in patients with ARDS and PAL.